Integrative technology of massage manipulations in physical rehabilitation of students with backbone pathology - V.I. Kotelevskiy (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Purpose:to analyze effectiveness of massage manipulations' integrative technology in physical rehabilitation of higher educational establishments' students with backbone pathology. Material: in the research 195 students of 19-20 years' age participated. All students had periodical initial neurological symptoms of functional pathology and first stage osteochondrosis in different parts of backbone. We conducted a course of 10 sessions of therapeutic massage. Results: the sense of massage integrative technology is that every specialist shall have certain optimal set of skills and knowledge in technique of manipulation sessions of massage. Integrative technology of massage manipulations consists of psycho-corrective and manipulation parts. It considers psycho-somatic, mechanical and reflex rehabilitation aspects of patho-genesis of backbone functional disorders and vertebral osteochondrosis. Conclusions: depending on pathological process or backbone functional state of every person (peculiarities of his (her) psycho-somatic status or, even, his (her) bents). Individual approach in choice of strategy, tactic and methodological provisioning of massage session shall be used.